Perception of shop floor employees regarding senior management support in lean projects and its relationship with initiatives success - Torres, Luis F.; Anholon, Rosley; Rampasso, Izabela Simon; Quelhas, Osvaldo L. G.; Leal Filho, Walter; Silva, Dirceu (Revista de Administração da UFSM, 2022)
Purpose – Over the years, the lean production philosophy has shown satisfactory results for companies from different sectors in different countries. Aiming to contribute to the knowledge base on the mentioned philosophy, this study aims to verify the perception of shop floor employees regarding senior management support in lean projects and its relationship with initiatives success. Design/methodology/approach – Through a literature review, 18 aspects of a lean journey were identified and divided into four constructs by a panel of specialists. This information was used to compose a questionnaire, and a survey was conducted with 198 shop floor employees of two auto parts companies. Data analysis was done via Structural Equation Modeling. Findings – As a general result, it was possible to prove that when employees perceive more significant support from senior management in lean projects, the greater is the perception of initiatives success. Therefore, it is interesting that the involvement of senior management occurs at all stages of the project. Originality/value – The results described here have practical implications, especially for managers interested in implementing lean projects; they must be aware of the importance of senior management support for the success of previous projects.